Permainan Domino dalam Pengajaran Mufradat di Madrasah Tsanawiyah - Milki Aan; Elia Rosa; Tsamratul Basiroh (Department of Arabic Education - Faculty of Educational Sciences, 2022)
This study begins with a shortage of learning methods and media used by teachers in the classroom. The goal of this study is to uncover teaching and learning procedures, as well as students' abilities before and after utilizing domino games, in order to determine the efficacy of learning vocabulary through domino games. The researchers utilized a quantitative technique and an experimental research strategy. A total of 55 pupils were included in the study. The Random Sampling Method was used for sampling. The researcher employed observation, interviews, written tests, and documentation to collect data. The T-test formula was employed to analyze the research data. The researchers found that the use of domino games in vocabulary learning in Islamic boarding schools was appropriate and successful based on the findings of this study.